Incidence and causative agents of chemical eye injuries in Switzerland. (26th November 2015) - Tschopp, Markus; Krähenbühl, Peter; Tappeiner, Christoph; Kupferschmidt, Hugo; Quarroz, Serge; Goldblum, David; Frueh, Beatrice E.
Abstract : Context : Chemical eye injuries are ophthalmological emergencies with a high risk of secondary complications and severe visual loss. Only limited epidemiological data for such injuries are available for many countries. Patients and methods : We performed two independent studies. The cause of chemical eye injuries was assessed with a prospective questionnaire study. Questionnaires were sent to all ophthalmologists in Switzerland. A total of 163 patients (205 eyes) were included, between December 2012 and October 2014. Independent of the questionnaire study, the incidence of chemical eye injuries was assessed with a retrospective cohort study design using the database of the mandatory accident insurance. Results : Ophthalmological questionnaires revealed that plaster/cement (20.5%), alkaline (12.2%) and acid (10.2%) solutions caused the highest number of chemical injuries. Only 2% of all injuries were classified as grade III and none as grade IV (Roper-Hall classification). The official toxicological information phone-hotline was contacted in 4.3% of cases. Using data from the accident insurance, an incidence of chemical eye injuries of about 50/100 000/year was found in the working population. Conclusion : Here, we present data on the involved agents of chemical eye injuries in Switzerland, and also the incidence of such injuries in the working population. This may also help to assess the need for further education programs and to improve and direct preventive measures.